Ultrasonography and Pregnancy Outcome in Threatened Abortion: A Prospective Observational Study - Singh, Maya; Kumar, Shishir; Lari, Nahid; Shankar, Daya (Student's Journal of Health Research Africa, 2025)
Background: Threatened abortion, marked by first-trimester vaginal bleeding, poses a risk for pregnancy loss and adverse outcomes. Ultrasonography is a key diagnostic tool for assessing fetal viability and identifying predictive markers such as fetal heart rate and crown-rump length. This study explores the role of ultrasonographic parameters in predicting miscarriage risk and guiding clinical management. Methods: This prospective observational study encompassed 100 pregnant women categorized into three groups based on first-trimester bleeding and ultrasonographic findings. Transvaginal ultrasonography assessed fetal heart rate, cervical length, and gestational sac characteristics. Statistical analyses evaluated the predictive value of sonographic markers for pregnancy outcomes. Results: Baseline characteristics were comparable among groups, but Group I had earlier and heavier bleeding. Group I also revealed lower fetal heart rates and crown-rump lengths, indicating poor pregnancy viability (p < 0.05). Adverse maternal and neonatal outcomes, including PROM, IUGR, and NICU admissions, were more frequent in Group II (p < 0.05). Early abnormal ultrasound markers were significantly associated with late pregnancy complications. Conclusion: Early first-trimester ultrasound markers, particularly fetal heart rate and crown-rump length, are strong predictors of adverse pregnancy outcomes. Identifying these markers can aid in risk stratification and timely intervention.